PAI Learning Model in Alam Ar-Ridho Elementary School - Faisol, Muhammad Aris; Raharjo, H; Mawanti, Dwi (Edukasi Islami : Jurnal Pendidikan Islam, 2021)
This research aimed to know the learning plan, implementation, and evaluation of Pendidikan Agama Islam/ Islamic Education (PAI) in Alam Ar-Ridho elementary school, Tembalang, Semarang. The methodology used is a qualitative field research using phenomenological approach. The data were collected through interview, observation, and documentation. The results found that the learning plan of PAI in Alam Ar-Ridho elementary was consisting of defining theme for one semester, defining title or theme, making theme analysis, making spider web, making weekly planning sheet, and writing daily activity. Alam Ar-Ridho elementary school used thematic integrated model using spider web or connecting one theme with some school subjects as PAI learning implementation. The learning materials in PAI were emphasize in aqeeda (believes), ‘akhlaq (moral), and fiqh (knowledge). While the learning concept had characteristics such as learning by doing, fun learning, and exploration. The learning evaluation was using written and spoken test technique along with practical tasks which referred to three aspects, such as; cognitive, affective, and psychometric. In summary, PAI learning in Alam Ar-Ridho elementary school had good plan, implementation and evaluation, however some things still needed to be enhanced and refined to make a better PAI learning.